Bactericidal activity of ceragenin CSA-13, CSA-44 and CSA-131 against bacteria causing bloodstream infections - Mańkowska, Angelika; Paprocka, Paulina; Suprewicz, Łukasz; Lesiak, Agata; Fortunka, Kamila; Król, Grzegorz; Spałek, Jakub; Okła, Sławomir; Durnaś, Bonita; Daniluk, Tamara; Piktel, Ewelina; Savage, Paul B.; et al. (Frontiers in Microbiology, 2025)
IntroductionThe constantly growing resistance of bacteria causing bloodstream infections and the lack of alternative antibiotics generate the need to develop new therapeutic strategies. In this study, the antibacterial properties of synthetic cholic acid derivatives ceragenins CSA-13, CSA-44 and CSA-131, custom-synthesized peptides human cathelicidin LL-37 peptide, synthetic WLBU2 peptide, and antimicrobial VFR12 peptide of human thrombin origin were evaluated to determine their potentials as therapeutic agents for bloodstream infections.MethodsMinimum inhibitory concentrations/minimum bactericidal concentrations (MIC/MBC) against clinical bacterial strains were measured and compared with activity of clinically used antibiotics colistin and vancomycin. Therapeutic potentials of the tested agents were assessed in the presence of 50% blood plasma, and their hemolytic properties were determined using human red blood cells (RCB). Additionally, the antimicrobial activity of CSA-13 against selected clinical strains was assessed using a killing assay. Plasma cytokine levels were determined, and endothelial cell confluent monolayer permeability was assessed using the FITC-dextran and measurement of transepithelial electrical resistance (TEER).ResultsUnder experimental conditions mimicking blood environment, ceragenins display higher antimicrobial activity compared to the cationic peptides regardless of the bacterial species. The presence of blood plasma slightly decreases the effect of ceragenins but does not significantly affect their antibacterial properties or their hemolytic activity, especially in case of ceragenin CSA-13. Furthermore, ceragenins at bactericidal concentrations do not induce hemolysis of red blood cells. CSA-13 dose-dependently regulates the permeability of human umbilical vein endothelial cells (HUVECs) monolayers as well as affects the secretion of cytokines, which may indicate its ability to modulate immune responses.ConclusionResults presented herein demonstrate the antibacterial activity of ceragenins against clinical strains of bacteria isolated from blood, their influence on the immune system and the integrity of the endothelial cell monolayer. Further studies are necessary to understand the cell signaling pathway governing these effects.